Toward an Emancipatory Understanding of Global Being: An Ideological, Ontological Critique of Globality - Beal, John Casey (Université d'Ottawa / University of Ottawa, 2011)
This Masters thesis conducts an ideological critique of the way 'the global' is constructed conceptually, particularly by transformative politics and the anti/alter global left. In addition it attempts to foreground the importance of ontological inquiry as an essential component of effective ideological critique. It has four chapters(plus an intro and conclusion); The first chapter looks at the ways that globality is currently constructed conceptually, both as an object of study by academia, and as an object of intervention by the global left. The analysis and critique in this chapter will establish the need for an ontologically informed approach to globality. The second chapter explores the precise meaning of the term 'ontology' as well as some of its common misuses by social science. It will focus on examining the ways that ontology is inherently political, and can be infiltrated by ideology. The third chapter draws heavily from the work of Zizek to develop a theoretical model for understanding the ontological production of globality, and how ideology is implicated. The fourth chapter attempts to take the conclusions from the theoretical model and use them to suggest alternative approaches to globality which might better the prospects for an effective transformative `global` politics. In particular this chapter draws heavily upon the Deleuzean notion of Immanence.
Keywords: Political Ontology; Globality; anti-globalization; Political Theory; the global left